BUMDes Management Oriented Toward Frugal Living: Lifestyle Transformation Toward a Resilient and Sustainable Village Economy - Susanto, Shobri Firman; Widyaswari, Monica; Mustakim, Mustakim; Zakariyah, M Fahmi (Universitas Negeri Padang, 2025)
Village development thru Village-Owned Enterprises (BUMDes) faces several challenges, ranging from low management capacity and economic literacy to minimal participation from village communities. This research aims to analyze the application of the frugal living principle in the management of Village-Owned Enterprises (BUMDes) in Bondowoso Regency as a transformation strategy toward a resilient and sustainable village economy. The research method used is a qualitative approach with a case study design on several active BUMDes selected purposively. Data were obtained thru in-depth interviews, participant observation, and documentation, which were then analyzed using the interactive model of Miles, Huberman, and Saldana 2014. The research findings indicate that the implementation of frugal living encompasses four main aspects: (1) economical, transparent, and accountable financial management; (2) utilization of local resources to enhance economic value and self-reliance; (3) needs-based business planning that promotes food security and financial literacy; and (4) innovation based on limitations thru the use of appropriate technology and the digitalization of public services. The conclusion of this study confirms that the principle of frugal living can be strategic for BUMDes to optimize limited resources, increase competitiveness, and achieve adaptive and sustainable village development.